The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0102-33062006000200010
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneidade florística e estrutural de remanescentes florestais da Área de Proteção Ambiental ao Sul da Região Metropolitana de Belo Horizonte (APA Sul-RMBH), Minas Gerais, Brasil

Abstract: ). A APA Sul-RMBH foi criada para compatibilizar a atividade econômica e a conservação do seu patrimônio natural, que abrange áreas de Floresta Estacional Semidecidual, Cerrado e Campo. O objetivo deste estudo foi caracterizar as comunidades arbóreas de alguns remanescentes florestais da APA quanto à estrutura, composição e similaridade florística. Foram estudadas oito áreas florestais distantes até 60 km entre si. Em cada área, foram amostrados 30 pontos quadrantes, tomando-se as medidas de circunferência e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
7
0
5
Order By: Relevance
“…However, Spósito & Stehmann (2006) found no significant correlations between geographic distance and floristic similarity among eight forest areas within the Quadrilátero Ferrífero region. The authors suggested that variations in temperature, rainfall and elevation, as well as the history of disturbance in particular, are the main factors related to the floristic variation.…”
Section: Discussionmentioning
confidence: 65%
“…However, Spósito & Stehmann (2006) found no significant correlations between geographic distance and floristic similarity among eight forest areas within the Quadrilátero Ferrífero region. The authors suggested that variations in temperature, rainfall and elevation, as well as the history of disturbance in particular, are the main factors related to the floristic variation.…”
Section: Discussionmentioning
confidence: 65%
“…It is worth highlighting that in the more mature fragments, where intersections with lower savanna communities were less frequent, the basal area value (23.71 m².ha -1 ) was superior to that obtained by Haidar et al (2005) (19,9 m².ha -1 ) and Imaña-Encinas et al (2007) (20.08 m².ha -1 ) in Goiás semi-deciduous forests. Thus, the greater representativeness of savanna phytophysiognomies in the fragments at an earlier stage of regeneration also gave rise to the differences and to species diversity, increasing the values of the latter to numbers closer to those proposed by Sposito & Stehmann (2006). Another source of biological variability can be the conjugation of the permanence of species related to the beginning of succession and of the recruitment of species from more advanced stages, in a facilitation model (Connell & Slatyer 1977), thus weakening possible dominance relationships among species.…”
Section: Resultsmentioning
confidence: 98%
“…Cerradão can act as a distribution limit for tree species of the Atlantic Domain (Costa & Araújo 2001) and share a high number of species with the latter (Rizzini 1979). Differences among the compositions of plant communities can derive from habitat heterogeneity, climatic and edaphic conditions and modifications, inter-specific interactions, and disturbance histories (Whittaker 1972;Ledru 1993;Oliveira-Filho et al 2001;Tabarelli et al 2004;Sposito & Stehmann 2006). Since they modify the demographic rates, the geographical distribution of plant populations and impact the extension of the biome zones (Ledru 1993;Ledru et al 1996;Ledru et al 1998;Hill & Curran 2003;Tabarelli et al 2004;Durigan & Ratter 2006;Malhi et al 2008;Lenoir et al 2008;Ledru et al 2009;Mantgem et al 2009), such factors interfere in the vegetation resilience and generate floristic dissimilarities.…”
Section: Resultsmentioning
confidence: 99%
“…Essas mesmas famílias foram as mais ricas em espécies no levantamento florístico realizado na EPDA-Peti por Pedralli & Teixeira (1997). As áreas amostradas confirmam a representatividade destas famílias nas florestas semidecíduas montanas da região centro-sul de Minas Gerais (Oliveira-Filho et al 1994a;Carvalho et al 1995;Botrel et al 2002;Espírito-Santo et al 2002;Souza et al 2003;Sposito & Stehmann 2006) e em florestas mesófilas semidecíduas de São Paulo (Leitão-Filho 1992).…”
Section: Resultsunclassified
“…Diferenças encontradas na composição florística do estrato arbóreo são características marcantes das florestas tropicais (Giraldo-Cañas 2000;Oliveira Filho & Fontes 2000). Sposito & Stehmann (2006) também encontraram alta heterogeneidade florística entre oito fragmentos de floresta na região metropolitana de Belo Horizonte, com distâncias entre as áreas até 60 km. Os níveis de alumínio encontrados nos solos das áreas amostradas são altos quando comparados a outras áreas de florestas estacionais semideciduais (Sposito & Stehmann 2006) (Tab.…”
Section: Resultsunclassified